Genetic heterogeneity in corpus callosum agenesis - Pânzaru, Monica-Cristina; Popa, Setalia; Lupu, Ancuta; Gavrilovici, Cristina; Lupu, Vasile Valeriu; Gorduza, Eusebiu Vlad (Frontiers in Genetics, 2022)
The corpus callosum is the largest white matter structure connecting the two cerebral hemispheres. Agenesis of the corpus callosum (ACC), complete or partial, is one of the most common cerebral malformations in humans with a reported incidence ranging between 1.8 per 10,000 livebirths to 230-600 per 10,000 in children and its presence is associated with neurodevelopmental disability. ACC may occur as an isolated anomaly or as a component of a complex disorder, caused by genetic changes, teratogenic exposures or vascular factors. Genetic causes are complex and include complete or partial chromosomal anomalies, autosomal dominant, autosomal recessive or X-linked monogenic disorders, which can be either de novo or inherited. The extreme genetic heterogeneity, illustrated by the large number of syndromes associated with ACC, highlight the underlying complexity of corpus callosum development. ACC is associated with a wide spectrum of clinical manifestations ranging from asymptomatic to neonatal death. The most common features are epilepsy, motor impairment and intellectual disability. The understanding of the genetic heterogeneity of ACC may be essential for the diagnosis, developing early intervention strategies, and informed family planning. This review summarizes our current understanding of the genetic heterogeneity in ACC and discusses latest discoveries.